Secagem periódica de soja em leito fixo - Defendi, Rafael Oliveira (2013)
Brazilian production and export of grains occupy a prominent position, as is the case of soybean which leads second place in the world ranking. One of the principal expenses in this products production is concentrated in grain drying. An alternative to reducing energy costs in this process is in the application of periodic operation which can lead to higher throughput and enhance the mass and energy transport. It is observed from the literature that there is a concentrated study of this operation in liquid stream modulation of trickle-bed reactors, which has shown that this operation can lead to higher conversions in comparison with the steady state one. In this context, one of the aims of this work is to study the periodic drying operation of soybeans in fixed bed using a mathematical model in comparison to conventional drying operation experiments made on laboratory scale in order to assess the benefits of each operation. Furthermore, other aims are to develop and validate a model that can describe the air temperature profile on its heating system by electrical resistances and to propose and validate a model that can estimate the global mass transfer coefficient validated by means of data obtained from drying kinetic experiments of soybeans on thin layer. The methodology was divided into 4 steps. The first one was to study the drying air heating system by electrical resistances relating the air temperature profile in steady state to the applied voltage on the heater and to the experimental conditions such as air flow and room temperature. It was proposed a mathematical model validated by means of experimental data and based on a balance energy made in the box heater which enabled to estimate the voltage needed to heat the air into a specific temperature. The ix second step was the soybeans drying kinetics on a thin layer study by measuring the water mass loss over time. It was adjusted a model by means of experimental data that described the global mass transfer coefficient as a function of the soybean moisture and the drying gas temperature. Then conventional drying operation of soybeans in fixed bed experiments were made and the results of the simulation of the two phases heterogeneous model were compared with gas moisture and temperature experimental data. Finally, in the last step it was simulated the periodic operation by means of the validated models in the same condition of conventional operation energy expenditure in order to compare the throughputs of each process.The obtained results showed that the air heating by electrical resistances model in steady state described the gas temperature profile with a maximum deviation around 2.2%. Meanwhile, the model used to estimate the global mass transfer coefficient described ideally the drying system behavior in the region where the mass transfer inside the soybean limits the process. However, this model has not fitted well during the first drying minutes where external effects are more significant over the system. Moreover, the two phases model showed to be appropriate to describe the soybean moisture and the soybean and gas temperature profiles for drying in fixed bed. Eventually the periodic operation simulation indicated that in some cases the modulation of the air temperature can lead to lower energy expenditures and higher yields depending on the amplitude, the period and the limiting process stage inherent to the soybean moisture.